Research Experiences in Education. An Introduction - Chiara Bove; Chiara Sità; Valentina Mazzoni; Paolo Sorzio (University of Bologna, 2016)
This paper is the introduction to the Focus of Encyclopaideia, which puts the spotlight on the topic of research methods in education, with a special attention on qualitative methods. The introduction presents the aims and the overview of the Focus, which is meant to be more a multi-vocal analysis of some of the issues emerging during the research work and the reflections they generate, rather than an abstract and homogeneous discourse. Each paper addresses a specific topic that is relevant to the research methodology in education, contextualizes it within a concrete inquiry and describes the researcher's reflective process of finding situated and rigorous solutions in order to contribute to the research validity.